Chondrocytes-induced SOX5/6/9 and TERT genes for articular cartilage tissue engineering: hype or hope? - Md Ali @ Tahir, Aisyah Hanani; Azhim, Azran; Sha'ban, Munirah (Persatuan Genetik Malaysia (Genetics Society of Malaysia), 2017)
Articular cartilage covers the ends of bones and forms a joint with another bone. This hyaline cartilage plays a significant role in weightbearing support system for the human body. This unique structure is aneural and avascular. It has limited capacity to regenerate once broken. If left untreated, this condition can worsen and later develop into degenerative joint disease known as osteoarthritis (OA). Until now, there is still no effective treatments to cure OA. There are many interventions available intended to reduce the progression of the disease. However, little is known about the treatments that can overcome the root of the problem. The emerging tissue engineering and regenerative medicine (TERM) field may offer an alternative therapeutic solution. The combination of three TERM components namely cell sources, biomaterial scaffolds, and signalling factors has been applied to produce biological cartilage substitute that restore, maintain, and improve the tissue functions. Reconstructing functional cartilage is a challenge for tissue engineers for decades. At the present human knowledge, the information of functional tissue formation is still limited and critically needed. Numerous attempts have been made in the TERM field to study factors that support specific cellular differentiation and quality tissue formation which include the use of gene transfer method. In cartilage research, SOX9 or (sex determining region Y)-box 9 is one of the essential transcriptional factors for cartilage development. SOX9 works with SOX5 and SOX6 in regulating chondrogenic lineage. These three factors, known as SOX-trio, play a crucial role in chondrogenesis. In a monolayer cell culture setting, replicative senescence limits chondrocytes in vitro expansion and differentiation. Other than using SOX-trio to promote the chondrogenic differentiation, the proliferative capacity of chondrocytes can be enhanced by telomerase reverse transcriptase (TERT), allowing for long-term culture. There is little evidence to suggest that interaction between SOX-trio and TERT in promoting chondrogenesis has been studied. The need for improved/thorough understanding of the cartilage healing process is also noted. Hence, this narrative review aims to identify patterns and trends in the literature concerning the crosstalk between the SOX-trio and TERT genes during chondrogenesis. It is hoped that the paper could